KARIKATUR GERAKAN ROMPI KUNING DI BELGIA - Andi Bau; Irianty Bandu; Andi Faisal (Universitas Hasanuddin, 2020)
This research is about the caricature analysis of the yellow vest movement in Belgium using a semiotic approach. This study aims to determine the meaning of connotation in the caricature of Les Gilets Jaunes by the caricature Oli. In addition, to know the form of depiction in caricature to convey meaning in caricature. Spurces of research data derivied from caricature web created by Oli, which is one of the caricaturist in Belgium. This research is a qualitative descriptive research. The results showed that the caricature related to Oli's Les Gilets Jaunes is a form of the reality of events that occurred. Some of Oli's works use analogy to convey the meaning to be conveyed.